Regulation of the Indian Port Sector - van Krimpen, Christiaan (World Bank, Washington, DC, 2013)
This report sets out various options for regulatory reform of the Indian port sector. The terms of reference from The World Bank require the Author making recommendations to the Ministry of Finance (Department of Economic Affairs) with respect to alternative institutional and legal options for regulation of the port sector in India as well as analysing key considerations in the regulation of this sector and the way they are being addressed in the Indian Ports (Consolidated) Act, 2010, which has been drafted recently. This report is solution-oriented and focuses on day-to-day problems of Indian port management. The problems of the Indian ports (including those of tariff regulation by TAMP) are well known, thoroughly analysed, described in detail and widely discussed in the port sector. A final solution for the restructuring of the sector has not yet been found. This report is written with a view to outlining various alternatives which may help the competent authorities to make final decisions on a new/revised port sector regulatory framework.